The term “populism” in Gramsci’s Prison Notebooks - Cingari, Salvatore (International Gramsci Journal, 2023)
The article opens by underlining that Laclau’s juxtaposition of Gramsci and populism is in part analogous to the operation carried out some decades ago by Alberto Asor Rosa and Rosario Romeo, although their evaluation was contrary to that of Laclau. We then attempt to demonstrate the limits of these interpretations, through a reconstruction of the national-popular theme in Gramsci: the correct interpretation of this category goes back not to the romantic imaginary of the Volkstum but to a development linked to the most enlightened circles of Russian culture. The national-popular thus alludes to a historically and nationally determined dimension, albeit one capable of universalization. This is confirmation of the non-“populist” nature of Gramsci’s argument. In his view, folklore has to be not idealized, but studied seriously, with the aim of superseding it in a paradigm that fuses together spontaneity and leadership, popular and high culture. As corroboration of this thesis we look at the ways in which the word “populism” is actually used in the Notebooks. The conclusion is that Gramsci, following Lenin’s example, referred “populism” to politico-cultural and literary phenomenologies unable to emancipate the people while, at the same time, he argued that it was necessary to understand and develop in a truly democratic perspective the social needs that populism expresses. This thesis is of great current relevance for those who believe that the social necessities lying behind the current “populist moment” must be understood in order to develop a higher “popular” perspective.